All‐Solution‐Processed Silver Nanowire Window Electrode‐Based Flexible Perovskite Solar Cells Enabled with Amorphous Metal Oxide Protection. Issue 9 (19th December 2017) - Lee, Eunsong; Ahn, Jihoon; Kwon, Hyeok‐Chan; Ma, Sunihl; Kim, Kyungmi; Yun, Seongcheol; Moon, Jooho
Abstract: Silver nanowire (AgNW)‐based transparent electrodes prepared via an all‐solution‐process are proposed as bottom electrodes in flexible perovskite solar cells (PVSCs). To enhance the chemical stability of AgNWs, a pinhole‐free amorphous aluminum doped zinc oxide ( a ‐AZO) protection layer is deposited on the AgNW network. Compared to its crystalline counterpart ( c ‐AZO), a ‐AZO substantially improves the chemical stability of the AgNW network. For the first time, it is observed that inadequately protected AgNWs can evanesce via diffusion, whereas a ‐AZO secures the integrity of AgNWs. When an optimally thick a ‐AZO layer is used, the a ‐AZO/AgNW/AZO composite electrode exhibits a transmittance of 88.6% at 550 nm and a sheet resistance of 11.86 Ω sq −1, which is comparable to that of commercial fluorine doped tin oxide. The PVSCs fabricated with a configuration of Au/spiro‐OMeTAD/CH3 NH3 PbI3 /ZnO/AZO/AgNW/AZO on rigid and flexible substrates can achieve power conversion efficiencies (PCEs) of 13.93% and 11.23%, respectively. The PVSC with the a ‐AZO/AgNW/AZO composite electrode retains 94% of its initial PCE after 400 bending iterations with a bending radius of 12.5 mm. The results clearly demonstrate the potential of AgNWs as bottom electrodes in flexible PVSCs, which can facilitate the commercialization and large‐scale deployment of PVSCs. Abstract : A pinhole‐free amorphous Al‐doped zinc oxide (AZO) protection layer dramatically enhances the chemical stability of silver nanowires (AgNWs). Using all‐solution‐processed amorphous AZO/AgNW/AZO transparent electrodes in flexible perovskite solar cells, it is possible to achieve a power conversion efficiency of 11.23%.